(untitled) (The Pakistan Development Review, 2020)
This paper argues that successful public policy requires engaged research developing ideas and evidence from diverse vantage points. Pakistan’s social science research remains fragmented, under-resourced and dependent on external agendas. We describe a five-year pilot programme to enhance Pakistan’s research culture. Seventy-two crowd-sourced and competitively-selected projects at 46 geographically dispersed institutions were supported. Provincial universities were empowered and networking with the better-placed metropolitan institutions proved mutually beneficial to scholarship. Substantial research outputs were completed in important areas of policy. We conclude that such multi-year commitments to review and network engagement are vital to strengthening policy capacity. Keywords: Pakistan; Research Community; Social Sciences; Networking; Competitive Grants